The Funding of The North Atlantic Treaty Organization - Matthijs, Herman (Advances in Social Sciences Research Journal, 2023)
This study examines the financing system of the budgets of the North Atlantic Treaty Organization (N.A.T.O.). The NATO is not a supranational organization, with partly exception of the military coordination by SHAPE, but an intergovernmental organization. So far, it’s the only existing military institution at present worldwide. This 2023 study concerns only the three internal NATO budgets. Therefore, this article is based at the only reference material available, namely the primary budgetary sources of the NATO. It must also be pointed out that NATO does prepare an annual report concerning the political and military situation. But there is no equivalent concerning an overview of its finances and administrative functioning. The aspects to be investigated are as follows: who is funding the NATO budgets and how? what happens with the money given to NATO? how is NATO’s budget prepared and approved? This article doesn’t treat the military budgets of the member states or the financing of the Parliamentary Assembly of the NATO.